Molecular Characterization of Lipopolysaccharide Binding to Human α-1-Acid Glycoprotein. (20th December 2012) - Huang, Johnny X.; Azad, Mohammad A. K.; Yuriev, Elizabeth; Baker, Mark A.; Nation, Roger L.; Li, Jian; Cooper, Matthew A.; Velkov, Tony
Abstract : The ability of AGP to bind circulating lipopolysaccharide (LPS) in plasma is believed to help reduce the proinflammatory effect of bacterial lipid A molecules. Here, for the first time we have characterized human AGP binding characteristics of the LPS from a number of pathogenic Gram-negative bacteria: Escherichia coli, Salmonella typhimurium, Klebsiella pneumonia, Pseudomonas aeruginosa, and Serratia marcescens . The binding affinity and structure activity relationships (SAR) of the AGP-LPS interactions were characterized by surface plasma resonance (SPR). In order to dissect the contribution of the lipid A, core oligosaccharide and O -antigen polysaccharide components of LPS, the AGP binding affinity of LPS from smooth strains, were compared to lipid A, Kdo2-lipid A, R a, R d, and R e rough LPS mutants. The SAR analysis enabled by the binding data suggested that, in addition to the important role played by the lipid A and core components of LPS, it is predominately the unique species- and strain-specific carbohydrate structure of the O -antigen polysaccharide that largely determines the binding affinity for AGP. Together, these data are consistent with the role of AGP in the binding and transport of LPS in plasma during acute-phase inflammatory responses to invading Gram-negative bacteria.